A Tale of Two Grass Species: Temperature Affects the Symbiosis of a Mutualistic Epichloë Endophyte in Both Tall Fescue and Perennial Ryegrass - Freitas, Priscila P.; Hampton, John G.; Rolston, M. Phil.; Glare, Travis R.; Miller, Poppy P.; Card, Stuart D. (Frontiers in Plant Science, 2020)
Many cool-season grasses form permanent, mutualistic symbioses with asexual Epichloë endophytes. These fungal symbionts often perform a protective role within the association as many strains produce secondary metabolites that deter certain mammalian and invertebrate herbivores. Although initially a serious issue for agriculture, due to mammalian toxins that manifested in major animal health issues, selected strains that provide abiotic stress protection to plants with minimal ill effects to livestock are now commercialized and routinely used to enhance pasture performance in many farming systems. These fungal endophytes and their grass hosts have coevolved over millions of years, and it is now generally accepted that most taxonomic groupings of Epichloë are confined to forming compatible associations (i.e. symptomless associations) with related grass genera within a tribe. The most desired compounds associated with Epichloë festucae var. lolii, an endophyte species associated with perennial ryegrass are peramine and epoxy-janthitrems. No other major secondary metabolites with invertebrate bioactivity have been identified within this association. However, other agriculturally beneficial compounds, such as lolines, have been discovered in related endophyte species that form associations with fescue grasses. A rationale therefore existed to develop novel grass-endophyte associations between loline-producing endophytes originally isolated from tall fescue with elite cultivars of perennial ryegrass to achieve a wider spectrum of insect bioactivity. A suitable loline-producing endophyte strain was selected and inoculated into perennial ryegrass. We hypothesed that endophyte transmission frequency, endophyte mycelial concentration and endophyte-derived alkaloid production would not differ between the original tall fescue host and the artificial association. This hypothesis was disproved, and our data strongly suggests that plant species significantly affects the plant-endophyte association. This effect became more apparent for transmission frequency and endophyte concentration as the plants matured. Overall, the viable endophyte infection frequency was greater in the tall fescue host than in perennial ryegrass, at all sampling dates. Additionally, temperature was found to be a significant factor affecting endophyte transmission frequency, endophyte mycelial concentration and alkaloid production. Implications for the development of novel grass-endophyte associations are discussed.